Integrating Liquid Biopsy and Radiomics to Monitor Clonal Heterogeneity of EGFR-Positive Non-Small Cell Lung Cancer - Cucchiara, Federico; Del Re, Marzia; Valleggi, Simona; Romei, Chiara; Petrini, Iacopo; Lucchesi, Maurizio; Crucitta, Stefania; Rofi, Eleonora; De Liperi, Annalisa; Chella, Antonio; Russo, Antonio; Danesi, Romano (Frontiers in Oncology, 2020)
Background: EGFR-positive Non-small Cell Lung Cancer (NSCLC) is a dynamic entity and tumor progression and resistance to tyrosine kinase inhibitors (TKIs) arises from the accumulation, over time and across different disease sites, of subclonal genetic mutations. For instance, the occurrence of EGFR T790M is associated with resistance to gefitinib, erlotinib, and afatinib, while EGFR C797S causes osimertinib to lose activity. Sensitive technologies as radiomics and liquid biopsy have great potential to monitor tumor heterogeneity since they are both minimally invasive, easy to perform, and can be repeated over patient’s follow-up, enabling the extraction of valuable information. Yet, to date, there are no reported cases associating methodologies during treatment management. Case presentation: In this case series, 7 patients with metastatic EGFR-positive NSCLC have been monitored during target therapy. Plasma-derived cell free DNA (cfDNA) was analyzed by a digital droplet PCR (ddPCR), while radiomic analyses were performed using the validated LifeX® software by looking at basal computed tomography (CT)-images. The dynamic of EGFR mutations in cfDNA was compared with that of radiomic features. Then, for each EGFR mutation, a radiomic signature was the sum of the correlated most predictive features, weighted by their corresponding regression coefficients for the least absolute shrinkage and selection operator (LASSO) model. The receiver operating characteristic (ROC) curve analyses were computed to estimate their diagnostic performance. The signatures achieved promising performance on predicting the presence of EGFR mutations (R2 = 0.447, p<0.001 for activating EGFR copies/ml; R2 = 0.301, p=0.003 for T790M copies/ml; and R2 = 0.354, p=0.001 for the total copies/ml), confirmed by ROC analysis. Conclusion: To our knowledge, these are the first cases to highlight a potentially promising strategy to detect clonal heterogeneity and ultimately identify patients at risk of progression during treatment. Together, radiomics and liquid biopsy could provide the appearance of new mutations and therefore address new therapeutic management.